Academic Senate Minutes 2007-05-10 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 4/26/07 approved. Advising Policy – First Reading. By-Laws revision: Duties of the Chairs delayed. Revision of Student Academic Probation, Disqualification, and Progress policy – First Reading. Resolution regarding the Allocation of Funds of the University for Assessment Tools such as Surveys and Focus Groups – First Reading. Special Report: Academic Council on International Programs – Robert Train. Motion on referendum for a vote of no confidence in the President amended and Approved. Good of the Order.